Analysis of Purchases, Receivables and Cash Flow on Profit Through a Cost Saving System as an Intervening Variable at PT. Kalam Leverage Mulia - Wigy Prayoga; Supardi Supardi; Wisnu Panggah Setiyono (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research aims to find out the results regarding the analysis of purchases, receivables and cash flow on profits through a cost savings system as an influencing variable for PT. Kalam noble leverage. This research uses quantitative methods. This method is usually carried out randomly, uses research instruments, and applies data or statistical analysis to test predetermined hypotheses. In this context, a quantitative approach is used by collecting data regarding purchases of project materials, receivables and cash flows during the 2018-2022 period. The data analysis technique uses the eviews 12 analysis method. The results of this research show that purchases and receivables do not affect the company's profit, while cash flow affects the company's profit.